2020
DOI: 10.3802/jgo.2020.31.e92
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 in gynecologic oncology: a Nationwide Italian Survey of the SIGO and MITO groups

Abstract: Objective Coronavirus disease 2019 (COVID-19) has caused rapid and drastic changes in cancer management. The Italian Society of Gynecology and Obstetrics (SIGO), and the Multicenter Italian Trials in Ovarian cancer and gynecologic malignancies (MITO) promoted a national survey aiming to evaluate the impact of COVID-19 on clinical activity of gynecologist oncologists and to assess the implementation of containment measures against COVID-19 diffusion. Methods The survey c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 20 publications
(26 reference statements)
1
30
0
Order By: Relevance
“…43 A national online survey was established by the Italian Society of Gynecology and Obstetrics, and the Multicenter Italian Trials in OC and gynecologic malignancies evaluated the impact of COVID-19 on the clinical activity of gynecologist oncologists and assessed the changes that have been implemented to reduce the risks of COVID-19 infection. 44 This study suggests that out of the 604 participants, 38% of the gynecologic surgeons expressed concern about the impact of COVID-19 on the treatment. Also, 21% of the total participants indicated a decrease in the use of laparoscopy.…”
Section: Effect On Ovarian Cancer Surgery and Treatmentmentioning
confidence: 88%
See 1 more Smart Citation
“…43 A national online survey was established by the Italian Society of Gynecology and Obstetrics, and the Multicenter Italian Trials in OC and gynecologic malignancies evaluated the impact of COVID-19 on the clinical activity of gynecologist oncologists and assessed the changes that have been implemented to reduce the risks of COVID-19 infection. 44 This study suggests that out of the 604 participants, 38% of the gynecologic surgeons expressed concern about the impact of COVID-19 on the treatment. Also, 21% of the total participants indicated a decrease in the use of laparoscopy.…”
Section: Effect On Ovarian Cancer Surgery and Treatmentmentioning
confidence: 88%
“…In addition, 20-25% of the total participants affirmed a decline in the use of radical surgical procedures. 44 It is suggested that only those procedures that are less demanding should be continued. While more extensive procedures should only be continued on an absolute necessary case.…”
Section: Effect On Ovarian Cancer Surgery and Treatmentmentioning
confidence: 99%
“…During the pandemic, it is necessary to find ways to protect health activities, especially in cancer patients, because some continue their own treatment algorithm while others continue the same treatment or delay treatment. Therefore, international cooperation is required [8].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The current ongoing COVID-19 outbreak is changing our practice as COVID-19 threatens to curtail patient access to evidence-based treatment. [8][9][10][11][12][13][14] Reducing the in-hospital risk of COVID-19 transmission is a priority. In the paper published in this issue, 15 the authors evaluated the impact of not performing delayed lymphoscintigraphic images for minimizing the in-hospital waiting time.…”
mentioning
confidence: 99%
“…Recently published recommendations on managing cancer patients during COVID 19 pandemic mostly focus on prioritization and optimization of treatments for these patients based on breast cancer type and preoperative staging. [8][9][10][11][12][13][14] Future studies will have to evaluate their overall impact on clinical outcomes.…”
mentioning
confidence: 99%